#TITLE_ALTERNATIVE# - MARCH ARITRA RAJAGUKGUK (NIM 13204206); Pembimbing: Dr.Ir. Suwarno, BASTIAN
Transformer insulation is one of the important thing to keep the transformer reliability. Therefore, we need such a maintenance method which able to determine the transformer insulation condition that we can determine the present transformer insulation condition and estimate for the the future condition. In order to determine performance of transformer insulation, there is a condition assessment method that can be used. Condition assessment method is separated into two main parts. The first part is risk assessment. In risk assessment, the failure mode and parameters which is involved to failure are determined. After that, from the parameters can be sorted which one that has more influence to create failure. Then, the second part of condition assessment is monitoring diagnosis technique. Monitoring diagnosis is a way to recognize parameters of Transformer Insulation. The parameters are water content, neutralizing number, breakdown voltage, interfacial tension, tan delta, oil color, furan content, TCG's condition, and CO2 content. Then the boundary value and weigthing factor for each parameter are defined. The boundary value is defined by using international standard, and the weighting factors are defined by Analytical Hierarchy Process. Finally, the result of risk assessment and monitoring diagnosis are combined to determine the actual condition of Transformer Insulation. This method is applied for condition assessment at IBT-1 and IBT-2 GITET Kembangan. The results are insulation condition is running to failure after first failure in September 2007 and After reclamation in april 2008, the transformer insulation condition is good.